Natural wave propagation in mine environments. - Lienard, M.
Theoretical and experimental aspects of the natural propagation of high-frequency waves in mines are presented. A narrow-band and a wide-band analysis have been carried out to determine the most important characteristics of the channel such as the longitudinal attenuation, the coherence bandwidth, and the delay spread of the impulse response in the various areas of an underground mine. The basic principle of a localization of a mobile has also been checked by determining the direction of arrival of the waves
Keywords: DoA estimation; Channel characteristics; Coherence bandwidth; Delay spread; Direction of arrival estimation; High-frequency waves; Impulse response; Longitudinal attenuation; Mine environments; Mobile localization; Narrow-band analysis; Natural wave propagation; Time interval measurement; Underground mine; Wide-band analysis